Properties of crimpable archwire hooks: a laboratory investigation - Johal, A; Harper, C R; Sherriff, M (European journal of orthodontics, 1999)
The aim of the present study was to utilize a strain gauge, which enabled the force applied to produce firmly attached crimpable hooks to rectangular stainless steel arch wires, to be measured. In vitro testing of two hooks, American Orthodontic (AO) and TP Orthodontic (TP), and two dimensions of stainless steel archwire, 0.019 x 0.025 and 0.018 x 0.025-inch, was carried out using an Instron Universal Testing machine. The results demonstrate that there was a significant difference in the behaviour of the two types of crimpable hooks, with almost twice the force needed to dislodge the TP hooks compared with the AO hooks (11.7 and 6.22 N, respectively). When using TP hooks attached to either 0.019 x 0.025 or 0.018 x 0.025-inch stainless steel wires, the archwire size makes little difference to the force required to produce movement. The clinical significance of these findings is discussed.